2014
DOI: 10.1097/sla.0000000000000494
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Cholangiocarcinoma or Mixed Hepatocellular-Cholangiocarcinoma in Patients Undergoing Liver Transplantation

Abstract: Patients with HCC-CC have similar survival to patients undergoing a transplant for HCC. Preoperative diagnosis of HCC-CC should not prompt the exclusion of these patients from transplant option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
117
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(137 citation statements)
references
References 31 publications
7
117
1
3
Order By: Relevance
“…53 Most recently, a multicenter study from Spain demonstrated better survival rates in 27 patients reaching 51% at 5 y. 54 The University of California Los Angeles group described promising data of neoadjuvant and adjuvant therapy combined with LT in the treatment of intrahepatic and hilar CCA. 55 They further proposed a prognostic scoring system to identify patients who may benefit from LT. 56 Seven independent risk factors (multifocal tumor, perineural invasion, infiltrative subtype, lack of neoadjuvant and/or adjuvant therapies, primary sclerosing cholangitis, hilar CCA, and lymphovascular invasion) were assigned certain risk score points based on the corresponding parameter estimate using the Cox model.…”
Section: -52mentioning
confidence: 99%
See 2 more Smart Citations
“…53 Most recently, a multicenter study from Spain demonstrated better survival rates in 27 patients reaching 51% at 5 y. 54 The University of California Los Angeles group described promising data of neoadjuvant and adjuvant therapy combined with LT in the treatment of intrahepatic and hilar CCA. 55 They further proposed a prognostic scoring system to identify patients who may benefit from LT. 56 Seven independent risk factors (multifocal tumor, perineural invasion, infiltrative subtype, lack of neoadjuvant and/or adjuvant therapies, primary sclerosing cholangitis, hilar CCA, and lymphovascular invasion) were assigned certain risk score points based on the corresponding parameter estimate using the Cox model.…”
Section: -52mentioning
confidence: 99%
“…Needle biopsy of the tumor should ideally be performed to confirm histology, although it might be difficult in a clinical setting. 54,62,63 A recent systematic review described marginal outcomes of LT for fibrolamellar HCC with 5-y survival rates ranging from 29-55%. 64 However, most of the collected cases were from the 1980s and early 1990s before the proposal of the Milan criteria.…”
Section: -52mentioning
confidence: 99%
See 1 more Smart Citation
“…Intense contrast uptake in the arterial phase followed by contrast washout in the venous phase, both on computed tomography or magnetic resonance, is considered diagnostic for HCC > 1 cm [9,14] . Nevertheless, on cirrhotic patients, small lesions may be misdiagnosed as being HCC and can in fact be intrahepatic cholangiocarcinomas (iCCA) or mixed hepatocellular-cholangiocarcinomas (HCC-CC), being their frequency much lower [15,16] . If the lesion does not show the typical HCC pattern on imaging, biopsy is mandatory [10] .…”
Section: Diagnosis Of Very Early Hccmentioning
confidence: 99%
“…This lower recurrence rate than previous reports could be attributed to the fact that 67% of patients had a single tumor and <20% showed microvascular invasion or satellite lesions. The authors concluded that a preoperative biopsy resulting in a diagnosis of combined HCC-cholangiocarcinoma should not exclude patients from LT. 15 Hepatic epithelioid hemangioendothelioma Hepatic epithelioid hemangioendothelioma was first described and characterized in 1982 as a low-grade malignant soft tissue tumor. 16 This disease has an incidence of 1per million, and diagnosis is often challenging.…”
Section: Introductionmentioning
confidence: 99%